Price-Endings When Prices Signal Quality - Stiving, Mark (Management Science, 2000)
This paper provides a theoretical explanation for why firms behave as though they use round prices to signal quality. By replacing the linear demand curve in Bagwell and Riordan's (1991) price as a signal of quality model with a kinked demand curve, and analyzing what price endings firms are most likely to use, the following observations can be made: (1) Firms that are using high prices to signal quality are more likely to set those prices at round numbers, and (2) price-endings themselves are not necessarily signals of quality. A simulation was conducted to demonstrate that these findings generally hold true even in the presence of demand spikes at 9-ending prices (e.g., Schindler and Kibarian 1996). Finally, empirical evidence is provided to demonstrate that firms tend to use more round prices for higherquality products, and that this relationship is even stronger for product categories where consumers are less able to detect the true level of quality prior to purchase.